Прикладний аспект історико-наукових досліджень: актуальність впровадження у вищу школу - Литвинко, А. С.; Пономаренко, Л. П. (НТУ "ХПІ", 2012)
У статті висвітлюється 10-річний досвід молодіжних конференцій з історії науки і техніки, які з 2002 р. проводить відділ історії науки і техніки Центру досліджень науково-технічного потенціалу та історії науки ім. Г.М.Доброва та фізико-математичний факультет Національного технічного університету України «Київський політехнічний інститут». Показано, що історико-наукові дослідження мають світоглядну спрямованість, тому участь у конференції сприяє усвідомленню студентською молоддю ролі науки, техніки та освіти, їх історії та сучасного стану. До складу оргкомітету конференції входять 4 академіки та 1 член-кореспондент НАН України, 1 академік та 1 член-кореспондент АПН Украни, 11 професорів. Чисельність учасників конференції зростала від 18 (з 3 установ) у 2002 р. до 104 (з 20 установ) у 2012 р. За 10 років у роботі конференції брали участь молоді вчені, аспіранти, студенти та учні старших класів з 14 міст та 32 вищих навчальних закладів, ліцеїв та наукових установ Росії, України, Польщі, США, Туреччини. Щорічно видаються збірники матеріалів конференцій.

The article highlights 10 years of youth conferences on the science and technology history studies, which from 2002 Department of Science History Studies of G.M.Dobrov Center for Scientific and Technological Potential and Science History Studies of National Academy of Science of Ukraine and Physics and Mathematics Department of National Technical University of Ukraine "Kyiv Polytechnic Institute" organized. It is shown that historical research formed scientific outlook, and participation in the conference assists understanding the role of science, technology and education, their history and current status. The Organizing Committee unites 4 academicians and 1 corresponding members NAS of Ukraine, 1 member and 1 corresponding member of the Academy of Pedagogical Science of Ukraine, 11 professors. The number of participants grew from 18 participants from 3 institutions in 2002 to 104 participants from 20 institutions in 2012. For 10 years young scientists, graduated and post-graduated students, and pupils from lyceums from 14 cities and 32 universities, high schools and scientific institutions of Russia, Ukraine, Poland, USA, Turkey attended the conference. Every year the Proceedings of conference are published.
Keywords: молодіжна конференція; доповідь; молоді науковці; історія науки і техніки; Historically-scientific researches; youth conference; presentation; young scientists; history of scitech